Autobiographies: A Way to Explore Student-Teachers’ Beliefs in a Teacher Education Program - Durán Narváez Norma Constanza (Profile Issues in Teachers' Professional Development, 2013)
<span style="font-size: 10.0pt; font-family: ";Verdana";,";sans-serif";; mso-fareast-font-family: ";Times New Roman";; mso-bidi-font-family: ";Times New Roman";; mso-ansi-language: EN-US; mso-fareast-language: ES-CO; mso-bidi-language: AR-SA;" lang="EN-US">Autobiographies depict with words life stories, personal experiences, and perceptions that allow researchers to deeply understand the way people see life, reflect, and construct meaning out of experiences. This article aims at describing the contributions of autobiographies as valuable resources in qualitative research when exploring people’s beliefs, personal knowledge, and changes as a result of experience and learning. This is all based on a research project carried out at a Colombian public university, where students from the undergraduate English teaching program wrote their language learning stories which were used as an instrument to garner data. The project also aims at demonstrating how these narratives exhibit human activity and diverse events that may have a significant effect on the epistemologies and methodologies of teacher education. <span style="font-size: 10.0pt; font-family: ";Verdana";,";sans-serif";; mso-fareast-font-family: ";Times New Roman";; mso-bidi-font-family: ";Times New Roman";; mso-ansi-language: EN-US; mso-fareast-language: ES-CO; mso-bidi-language: AR-SA;" lang="EN-US">Las autobiografías perfilan con palabras las historias de vida, experiencias personales y percepciones que brindan a los investigadores una profunda comprensión de la manera como las personas ven la vida, reflexionan y construyen significado a partir de esas experiencias. Este artículo tiene como objetivo describir las contribuciones de las autobiografías como recursos valiosos en la investigación cualitativa por cuanto son un medio para explorar las creencias, el conocimiento personal y los cambios en los individuos como resultado de la experiencia y el aprendizaje. El presente trabajo se basa en una investigación realizada en una universidad pública colombiana, en la que estudiantes de la Licenciatura en Inglés narraron sus historias sobre el aprendizaje de la lengua; narraciones que fueron usadas como instrumentos para la recolección de información. Adicionalmente, se busca demostrar cómo dichas narrativas describen la actividad humana y diversos eventos que pudiesen tener un efecto significativo en la construcción epistemológica y metodológica en la formación de docentes.